Identity, mediation, and the cunning of capital - Maitra, Ani (Critical insurgencies., 2020)
"In Identity, Mediation, and the Cunning of Capital, Ani Maitra calls for an urgent reevaluation of identity politics as an aesthetic maneuver regulated by capitalism. A dominant critical trend in the humanities, Maitra argues, is to dismiss or embrace identity through the formal properties of a privileged aesthetic medium like literature, cinema, or even the performative body. In contrast, he demonstrates that identity politics becomes unavoidably real and material only because the minoritized subject is split between multiple sites of mediation-visual, linguistic, and sonic-while remaining firmly tethered to capitalism's hierarchical logic of value production. Only in the interstices of media can we track the aesthetic conversion of identitarian difference into value, marked by the inequities of race, class, gender, and/or sexuality. Maitra's archive is reflexively transnational and multimodal. Moving from anticolonial polemics to psychoanalysis to diasporic experimental literature to postcolonial feminist and queer media, he lays bare the cunning through which capitalism produces and fragments identity through an intermedial "aesthetic dissonance" with the commodity form. Maitra's novel contribution to theories of identity and, indeed, to the concept of "mediation" will interest a wide range of scholars in media studies, critical race and postcolonial studies, and critical aesthetics"--